Binning enables efficient host genome reconstruction in cnidarian holobionts. Issue 7 (18th July 2018) - Celis, Juan Sebastián; Wibberg, Daniel; Ramírez-Portilla, Catalina; Rupp, Oliver; Sczyrba, Alexander; Winkler, Anika; Kalinowski, Jörn; Wilke, Thomas
Abstract: Background: Many cnidarians, including stony corals, engage in complex symbiotic associations, comprising the eukaryotic host, photosynthetic algae, and highly diverse microbial communities—together referred to as holobiont. This taxonomic complexity makes sequencing and assembling coral host genomes extremely challenging. Therefore, previous cnidarian genomic projects were based on symbiont-free tissue samples. However, this approach may not be applicable to the majority of cnidarian species for ecological reasons. We therefore evaluated the performance of an alternative method based on sequence binning for reconstructing the genome of the stony coral Porites rus from a hologenomic sample and compared it to traditional approaches. Results: Our results demonstrate that binning performs well for hologenomic data, producing sufficient reads for assembling the draft genome of P. rus . An assembly evaluation based on operational criteria showed results that were comparable to symbiont-free approaches in terms of completeness and usefulness, despite a high degree of fragmentation in our assembly. In addition, we found that binning provides sufficient data for exploratory k -mer estimation of genomic features, such as genome size and heterozygosity. Conclusions: Binning constitutes a powerful approach for disentangling taxonomically complex coral hologenomes. Considering the recent decline of coral reefs on the one hand and previous limitations to coral genome sequencing on the other hand, binning may facilitate rapid and reliable genome assembly. This study also provides an important milestone in advancing binning from the metagenomic to the hologenomic and from the prokaryotic to the eukaryotic level.